2020
DOI: 10.1111/njb.02699
|View full text |Cite
|
Sign up to set email alerts
|

Oreocharis argentifolia (Gesneriaceae), a new species from the karst region in southeastern Yunnan, China

Abstract: A new species of Gesneriaceae, Oreocharis argentifolia Lei Cai & Z.L.Dao from Mengzi City, Yunnan Province, China, is described and illustrated. The new species is morphologically most similar to O. panzhouensis Lei Cai, Y.Guo & F.Wen in plant habit, number of stigma lobes and stamens, and the shape of the calyx, but differs in the shape of the leaf blade, indumentum, shape and color of corolla and the adnate position of the filaments. A detailed description, color photographs, distribution and habitat, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…After careful observation of the characteristics of its flowers, such as nearly cylindric corolla tube and 2‐lipped limb, meristem stamens 4, narrow oblong anthers with parallel thecae, we concluded that it belongs to the genus Oreocharis . However, after comprehensive morphological study, consultation of specimens and relevant literature (Wang 1987, Tan et al 2013, 2014, Wei et al 2016, Chen et al 2017, 2018, 2020a, b2020b, Yang et al 2019, Cai and Dao 2020), we concluded that it was an undescribed species. Hence it is described here as a new species with detailed description, color photographs, distribution and habitat, as well as a discussion about its morphological relationship with similar species.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…After careful observation of the characteristics of its flowers, such as nearly cylindric corolla tube and 2‐lipped limb, meristem stamens 4, narrow oblong anthers with parallel thecae, we concluded that it belongs to the genus Oreocharis . However, after comprehensive morphological study, consultation of specimens and relevant literature (Wang 1987, Tan et al 2013, 2014, Wei et al 2016, Chen et al 2017, 2018, 2020a, b2020b, Yang et al 2019, Cai and Dao 2020), we concluded that it was an undescribed species. Hence it is described here as a new species with detailed description, color photographs, distribution and habitat, as well as a discussion about its morphological relationship with similar species.…”
Section: Introductionmentioning
confidence: 83%
“…We took photographs, collected specimens and introduce the living plants to the greenhouse of Guangxi Institute of Botany for careful cultivation. In early September 2020, we observed this species has blossomed in the greenhouse, after comprehensive morphological study, consulted the relevant literature (Wang 1987;Tan et al 2013Tan et al , 2014Wei et al 2016;Chen et al 2017Chen et al , 2018Chen et al 2020a, Chen et al 2020bYang et al 2019;Pan et al 2019;Cai and Dao 2020), we concluded that this species belongs to Oreocharis, and is an undescribed species. Since then, we have conducted many field studies on it and collected materials for flowering and fruiting.…”
Section: Introductionmentioning
confidence: 90%
“…Detailed morphological comparisons with the protologues and type specimens of all previously-described species of Oreocharis s.l. ( Pan 1987 ; Wang et al 1990 , 1998 ; Li and Wang 2004 ; Wei et al 2010 ; Liu et al 2012 ; Chen et al 2013 , 2014 , 2015 , 2016 , 2017 , 2018 ; Tan et al 2013 , 2015 ; Möller et al 2014 , 2018 ; Möller 2015 ; Li and Li 2015 ; Yang et al 2015a , 2015b , 2017 , 2019 ; Wei et al 2016 ; Li et al 2017 ; Do et al 2017 ; Cai et al 2019 , 2020 ; Cai and Dao 2020 ) revealed that these specimens do not match with any known Oreocharis species. Therefore, we confirmed that these specimens represent a new species, which is here described and illustrated, namely O.…”
Section: Introductionmentioning
confidence: 99%
“…After consulting some Gesneriaceae monographs (Li and Wang 2004;Wei et al 2010) and comparing the species with other described congeners (Wang et al 1990(Wang et al , 1998Chen et al 2016;Wei et al 2016;Do et al 2017;Li et al 2017;Yang et al 2017;Guo et al 2018;Möller et al 2018;Pan et al 2019;Yang et al 2019;Cai and Dao 2020;Chen et al 2020;Qin et al 2020) and specimens of Gesneriaceae deposited at IBSC, IBK, KUN, PE, US and VMN, we referenced the older specimen information and articles from other species. Then we confirmed that it is a new species.…”
Section: Introductionmentioning
confidence: 99%